The Concept of "Character" in Literary Studies. Character System in Literature - Shuhrat ugli , Nuridinov Zukhriddin (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2025)
This article examines the concept of "character" from various literary perspectives. The main character classification systems proposed by researchers such as A.B. Yesin and N.L. Vershinina were analyzed. Special attention is paid to the structure of the character system in literary works. During the study, it was established that both classifications distinguish main, secondary, and episodic characters, however, N.L. Vershinina’s system is the most detailed.